Providing Adapted Contextual Information in an Overlay Vehicular Network - José Santa; Andrés Muñoz; Antonio F. Gómez-Skarmeta (International Journal of Digital Multimedia Broadcasting)
Current vehicular networks are developed upon commercial solutions based on cellular networks (CNs) or vehicular ad-hoc networks (VANETs), both present in numerous research proposals. Current approximations are not enough to cover the communication necessities of several applications at the same time, and they are not suitable for future vehicular pervasive services. The vehicular network presented in this paper fills the existent gap between solutions lacking in flexibility, mainly supported by an infrastructure deployment, and those highly local and distributed, such as sole-VANET approximations. In this manner, an overlay communication platform which can work over the CN basis has been designed and developed. This architecture is complemented by an additional support of an information system located at the infrastructure side. Moreover, since most of the information received from current notification services is not relevant for the driver, an additional subsystem has been devised to provide adapted information to users. This has been carried out by means of an ontology model which represents users' preferences and contextual information. Finally, using a whole prototype of the telematic platform, the performance of this interring process has been evaluated to point out its impact on the system operation.